The Cognitive Bridge: Analyzing The Mediating Role Of Psychological Well-Being On The Impact of Free Nutritious Meals on Student Learning Outcomes - Lily Anisetiawan; Vika Annisa Qurrata; Thomas Sosecco (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the effect of the Free Nutritious Meals Program (FNMP) on Student Learning Outcomes (SLO) with Psychological Well-being (PWB) as a mediating variable. The background of this research is driven by the increasing implementation of nutritious food programs in schools, but their effectiveness in improving student learning outcomes still shows variation and does not have consistent conclusions in scientific studies. A quantitative approach with an explanatory survey design was used in this research, involving 108 grade XII students from SMK Negeri 3 Balikpapan as the sample. The research instrument was a Likert scale questionnaire, and data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that FNMP had a positive and significant effect on PWB, and PWB had a significant effect on SLO. Additionally, it was found that FNMP does not directly increase SLO significantly without the involvement of psychological well-being factors. This finding confirms that PWB plays a full mediating role in the relationship between FNMP and SLO. The better the implementation of FNMP, the higher the level of students' psychological well-being, which ultimately improves their learning outcomes. This study concludes that FNMP should not only be understood as a nutritional intervention, but also as a psychological intervention that focuses on improving students' emotional well-being in order to optimize its academic impact. Practically speaking, schools and policymakers are advised to integrate free meal programs with strategies that support students' psychological well-being.